Real-time systems development - Williams, Rob, 1948- (Oxford ; Burlington, MA : Elsevier Butterworth-Heinemann, 2006)
Real-time Systems Development is a text for computing students who want to understand more about the development of software for real-time applications, involving concurrent programming, multi-tasking, data i/o and embedded processors. The book has been written to cover single semester final year undergraduate options or MSc modules in the area of real-time systems design and implementation. Assuming a certain level of general systems design and programming experience, this text will extend students knowledge and skills into an area of computing which has increasing relevance in a modern world of telecommunications and intelligent equipment using embedded microcontrollers. * Concise treatment delivers material in manageable sections * Includes handy glossary, references and practical exercises based on familiar scenarios * Supporting website contains slides, solutions to problems and software examples.
Introduction to real-time systems -- Implementing simple real-time systems -- Basic input and output -- Cyclic executives for bare hardware -- Finite state machines : design tool -- Finite state machines : implementation options -- Why multi-task? -- Task communication and synchronization -- Real-time executives -- Using input/output interfaces -- Structured design for real-time systems -- Designing for multi-tasking -- UML for real-time systems -- Object-oriented approach for real-time systems -- System integrity -- Languages for RTS development : C, Ada and Java -- Cross-development techniques -- Microcontroller embedded systems -- Linux device drivers -- Hardware/software co-design.
Includes bibliographical references and index.
Keywords: Real-time programming; Electronic books